Effect of Cascara Proportion on Melting Time and Hedonic Toward Color Preference of Ice Cream - Yoyok Budi Pramono; Monica Pratiwi Simbolon; Siti Susanti (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2021)
The aim of this research was to determine the effect of adding different concentrations of cascara extract on the melting time and color of ice cream. The material used in this study was cow's milk as raw material for making ice cream with different extract concentration treatments. The research method used was a Completely Randomized Design (CRD) with 5 treatments and 4 repetitions. Variations in extract concentration were 0%, 10%, 20%, 30%, 40%. The melting time test data were analyzed using Analysis of Variance (ANOVA) with a confidence level of 95% and if there is a real influence then proceed with the Duncan Multiple Range Test (DMRT). Data of ice cream color test results were analyzed using the Kruskal Wallis non-parametric test with a confidence level of 95% and if there is a real influence, then proceed with the Mann-Whitney test. The results showed that different concentrations of Cascara Arabica extract had a significant effect (p<0.05) on the melting time and color of ice cream products. The increased concentration of cascara extract, the longer the melting time. Ice cream with an extract concentration of 40% was the product with the best treatment because it had the longest melting time and the color of the ice cream was favored by panelists.